Activation of Polycystic Kidney Disease-2-like 1 (PKD2L1)-PKD1L3 Complex by Acid in Mouse Taste Cells - Kawaguchi, Hitoshi (American Society for Biochemistry and Molecular Biology, 2010)
Five basic tastes (bitter, sweet, umami, salty, and sour) are detected in the four taste areas where taste buds reside. Although molecular mechanisms for detecting bitter, sweet, and umami have been well clarified, those for sour and salty remain poorly understood. Several channels including acid-sensing ion channels have been proposed as candidate sour receptors, but they do not encompass all sour-sensing abilities in vivo. We recently reported a novel candidate for sour sensing, the polycystic kidney disease-2-like 1 (PKD2L1)-PKD1L3 channel complex. This channel is not a traditional ligand-gated channel and is gated open only after removal of an acid stimulus, called an off response. Here we show that off responses upon acid stimulus are clearly observed in native taste cells from circumvallate, but not fungiform papillae, of glutamate decarboxylase 67-green fluorescent protein (GAD67-GFP) knock-in mice, from which Type III taste cells can be visualized, using Ca(2+) imaging and patch clamp methods. Off responses were detected in most cells where PKD2L1 immunoreactivity was observed. Interestingly, the pH threshold for acid-evoked intracellular Ca(2+) increase was around 5.0, a value much higher than that observed in HEK293 cells expressing the PKD2L1-PKD1L3 complex. Thus, PKD2L1-PKD1L3-mediated acid-evoked off responses occurred both in HEK293 cells and in native taste cells, suggesting the involvement of the PKD2L1-PKD1L3 complex in acid sensing in vivo.